2011
DOI: 10.1371/journal.pntd.0001365
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Sylvatic Foci of the Main Vector of Chagas Disease Triatoma infestans: Threats to the Vector Elimination Campaign?

Abstract: BackgroundEstablishing the sources of reinfestation after residual insecticide spraying is crucial for vector elimination programs. Triatoma infestans, traditionally considered to be limited to domestic or peridomestic (abbreviated as D/PD) habitats throughout most of its range, is the target of an elimination program that has achieved limited success in the Gran Chaco region in South America.Methodology/Principal FindingsDuring a two-year period we conducted semi-annual searches for triatomine bugs in every D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 75 publications
4
86
2
3
Order By: Relevance
“…This process apparently occurred in southern Brazil and included Didelphis opossums and T. sordida. 48 The repeated findings of sylvatic colonies of Triatoma infestans in the Gran Chaco [49][50][51] suggest that domestic or peridomestic parasite or vector spillovers occur.…”
Section: Discussionmentioning
confidence: 99%
“…This process apparently occurred in southern Brazil and included Didelphis opossums and T. sordida. 48 The repeated findings of sylvatic colonies of Triatoma infestans in the Gran Chaco [49][50][51] suggest that domestic or peridomestic parasite or vector spillovers occur.…”
Section: Discussionmentioning
confidence: 99%
“…The flow of insects between sylvatic and domestic habitat is of great importance in vector control because sylvatic populations can be a source of reinfestation of dwellings and are more widespread than was previously thought. Ceballos et al (2011) showed that some T. infestans wild colonies were closely connected to domestic conspecifics in the Argentinean Chaco and that sylvatic habitats may provide a transient or permanent refuge after control interventions, functioning as sources for domestic/peridomestic reinfestation. Given the possible large numbers of wild populations in the dwelling-reinfestation process, it is imperative that we fully understand the origin of the resistance to insecticide observed in wild populations of T. infestans and more accurately measure the flow of insects between wild and domestic foci through further genetic analyses and behavioural studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, discoveries of sylvatic foci in Argentina, Paraguay and Chile show that sylvatic populations of T. infestans are more widespread than initially described (Ceballos et al 2009, Bacigalupo et al 2010, Rolón et al 2011. It is worth noting that these sylvatic populations have the potential to jeopardise control efforts because of possible free insect movements between the sylvatic environment and dwellings (Noireau et al 2005, Ceballos et al 2011. Because wild populations may recolonise insecticide-treated areas, it is extremely important to know their response to insecticides.…”
mentioning
confidence: 99%
“…2010) and to the south in the arid, lowland Chaco region (Ceballos et al . 2011; Waleckx et al . 2012), where their potential for domestic re‐invasion threatens the success of the National Control Programme (Noireau et al .…”
Section: Introductionmentioning
confidence: 99%